(untitled) (Web of Teachers: Inderscience Research, 2024)
This article describes the concept of "Forward Rate" used in foreign exchange markets. This understanding helps to understand how important it is in predicting the future prices of the currency and planning financial activities. The article shows how the forward rate works, how it can be used, through examples.